Exploration of job satisfaction among technical employees of quantity surveying firms in Malaysia - Tan, Chin Keng; Mohamed Nor, Nik Nur Azirah; Yeoh, Kah Ching (International Academic Institute for Science and Technology, 2018)
Within the framework of human resource management, this study is focusing on the issue of job satisfaction in the context of Quantity Surveying firms. In relation to the Quantity Surveying firms in Malaysia, the objectives of this research is to explore the level of job satisfaction among the technical employees. Semi-structured interview is the method used to collect data for this study. The interview was conducted with five (5) technical employees and five (5) employees from Human Resources department of Quantity Surveying firms in Kuala Lumpur. The research findings conclude that generally, technical employees are having job satisfaction on the constructs studied, i.e. opportunities and rewards, social interaction, working relationship with immediate superior, nature of work, organizational factors and attitude towards work.